Resiko keracunan Merkuri (Hg) pada pekerja penambangan emas tanpa izin (peti) didesa cisarua kecamatan nanggung kabupaten bogor - Ela Laelasari Sakkir; Nita Ratna Junita; Arif Sumantri (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT The use of mercury in gold processing can cause health effect, such as incident of mercury poisoning. Based on preliminary studies of 10 workers mining at Cisarua Village Nanggung Subdistrict, there were 8 workers who have mercury poisoning. This research was a quantitative research with cross sectional approach. The samples of this study were 40 workers of illegal gold mining at Cisarua Village, Nanggung Subdistrict. The samples were taken by using accidental sampling technique. The research data was collected by interview, observational and measurement of mercury level in hair of workers. The independent variables in this study were age, nutritional status, working period per year, working time in a day, working activity, and consumption of fish. The dependent variable was the incidence of mercury poisoning. The data were processed by using independent t, mann- whitney u test and chi square test at α 5%. The results of this research indicate that were 24 workers (60%) have mercury poisoning. Then, based on the results of bivariate analysis was known that there were two independent variables have significant correlation with mercury poisoning. That variables were working period per year (p value=0,0005) and working time in a day (p value=0,035). Key words: mercury, poisoning, workers, maining